Precision medicine on a budget in Africa: using existing genetic data to mitigate adverse drug reactions to conventional cancer drugs - Djomkam Zune, Alexandra Lindsey; Olwal, Charles Ochieng’; Agbeli, Emmanuel; Diallo, Abdoulaye Baniré; Amoako, Emmanuella; Bediako, Yaw; Paemka, Lily (Frontiers in Bioinformatics, 2025)
Variations in drug-metabolizing enzymes and transporters are associated with adverse drug reactions (ADRs). ADRs to cancer drugs can differ among populations owing to environmental and genetic differences. Due to limited resources and prohibitive costs associated with drug development, African countries rely on cancer drugs developed from non-African genetic backgrounds. Black Africans carry a high burden of ADRs partly because of the use of poorly optimized drugs. Black Africans are the least studied population despite being the most genetically diverse. There is a profound lack of pharmacogenetic studies in Black African populations, necessitating an urgent need for pharmacogenomic studies in Black African populations to optimize dosing and minimize ADRs. Using two common generic cancer drugs, capecitabine and cyclophosphamide, we leveraged the PharmGKB platform and several genomic databases to highlight the need for pharmacogenomic studies in Africa. Our computational approach identifies previously reported and unreported toxicity- and efficacy-associated variants that are overrepresented or underrepresented in Black Africans relative to other ethnicities. These findings suggest that capecitabine and cyclophosphamide may not work optimally and/or may predispose Black Africans to ADRs. This underscores the need for population-based drug screening and development to minimize ADRs and guarantee better treatment outcomes. Since Black Africans are currently underrepresented in genomic studies, African scientists could adopt our low-cost approach to evaluate the suitability of existing drugs for treating diseases. However, in the long term, African scientists must initiate large-scale genomic studies that will drive the discovery of African-tailored drugs and promote the implementation of precision medicine on the continent.